GENERATION Z: MEDIA CONSUMPTION AND MIL - Anthoula Baliou; Chryssa Lazou; Nıkolaos Panagıotou (İmgelem)
The aim of this paper is to discuss Generation Z (the generation of people born in the late 1990s and early 2000s) media consumption patterns and their understanding and adoption of MIL. Digital and media literacy are recognized as tools of particular importance in strengthening young people’s civic participation and understanding of the news. This element has become increasingly important with the proliferation of mis/disinformation especially on digital platforms. Generation Z, like Millennials before them, spend considerable screen time. They are native technophiles that have had touchscreen devices and smart features from their very early years. That is a critical factor in their media consumption as they reach adulthood. Yet, while they swipe, tap, like, and share, they’re aware of how much attention their tech is getting. Through a study regarding media and information literacy among Generation Z (those who are 26 or younger) we provide data about the youngest generation in Greece (Generation Z) regarding their media and information consumption, and their relationship with MIL, Disinformation in relation with a critical factor that of reliability and trust in news sources and institutions.